2018
DOI: 10.1016/j.jconrel.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intraocular pressure reduction with intracameral polycaprolactone glaucoma devices that deliver a novel anti-glaucoma agent

Abstract: Long-term treatment of glaucoma, a major leading cause of blindness, is challenging due to poor patient compliance. Therefore, a drug delivery device that can achieve drug release over several months can be highly beneficial for glaucoma management. Here, we evaluate the long-term pharmacokinetics and therapeutic efficacy of polycaprolactone intracameral drug delivery devices in rabbit eyes. Our study showed that a single drug delivery device loaded with a proprietary hypotensive agent, DE-117, reduced intraoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…By providing sustained IOP-lowering effects, drug-delivery systems such as Bimatoprost SR may help to address this unmet need. These new delivery systems may delay the need for more invasive (surgical) treatment by more precisely targeting the drug to sites of action [30,35,36], while providing IOP-lowering effects and tolerability profiles comparable to those of topical therapy [28,37,38]. Other sustained-release products are in various phases of clinical development, including ENV515 (Envisia Therapeutics, Durham, NC, USA), OTX-TIC (Ocular Therapeutix, Bedford, MA, USA), and iDose (Glaukos Corporation, Laguna Hills, CA, USA) for intracameral delivery of travoprost.…”
Section: Discussionmentioning
confidence: 99%
“…By providing sustained IOP-lowering effects, drug-delivery systems such as Bimatoprost SR may help to address this unmet need. These new delivery systems may delay the need for more invasive (surgical) treatment by more precisely targeting the drug to sites of action [30,35,36], while providing IOP-lowering effects and tolerability profiles comparable to those of topical therapy [28,37,38]. Other sustained-release products are in various phases of clinical development, including ENV515 (Envisia Therapeutics, Durham, NC, USA), OTX-TIC (Ocular Therapeutix, Bedford, MA, USA), and iDose (Glaukos Corporation, Laguna Hills, CA, USA) for intracameral delivery of travoprost.…”
Section: Discussionmentioning
confidence: 99%
“…[45] In a more recent study in 16 normotensive rabbits, the same group found a statistically significant IOP reduction in eyes implanted with the DE-117 PLC compared with untreated eyes and placebo PCL devices. [46] Tolerability was good and rates of iris trauma and hyphema during the implantation procedure were lower (19%) than in the previous study (29%). One DE-117 implant migrated to the angle, but this had no obvious effect on its activity.…”
Section: De-117mentioning
confidence: 48%
“…Long acting intracameral implants have been developed as an alternative for the use of anti-glaucoma eyedrops that have poor patient compliance in the clinical practice [34,35]. Biologicals cannot be used as eyedrops for anterior segment treatments, because they do not permeate across the cornea and the bioavailability after sub-conjunctival delivery is less than 10% [7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the aqueous humor bioavailability of an intravitreal protein drug is almost complete, because nearly a whole dose is eliminated via the anterior route. Sampling of aqueous humor has also been used as an indicator of drug activity for intravitreally administered protein drugs, which also applies in humans [34].…”
Section: Discussionmentioning
confidence: 99%